The Role of National Values in the Formation of Social Competence in Students - Q. V. Nishonboeva (International Journal on Integrated Education, 2022)
This article is dedicated to the concept of competence and professional competence and its entry into science, as well as the competence approach that is widely introduced to all normative requirements of the stages of the educational system of our republic, scientific conclusions are given on the importance of competence approaches in science, education and practice. Also, the origin, types, content, practical importance of the competence approach in education and what should be paid attention to in the future are revealed.